University students’ preparation towards building knowledge economy in Africa: A case of Universities in Ghana - Frank Quansah1; Ebenezer Appiah2; Vera Rosemary Ankoma-Sey3 (University of Cape Coast, 2019)
For a country to develop, universities need to prepare students to be confident in facing the demands of the contemporary world of work. This paper focuses on examining how well universities are preparing students in Ghana in building a knowledge economy. The paper further explored the relationships among university preparation, students’ preparation, and confidence of students. Using a cross-sectional survey design, data was gathered from 690 students from three public universities in Ghana, through a multi-stage sampling technique. A closed-ended questionnaire was used as the main data collection instrument. It was found that students prepared themselves towards a knowledge economy. Although the universities made efforts in preparing students, there were still lapses in preparing students towards a knowledge economy. Further analysis revealed that students were not confident enough to face the demands of a knowledge economy. Analysis from the mediation analysis using bootstrapping approach (5000 bootstrap samples), revealed that university preparation of students significantly mediated the relationship between students’ personal preparation and confidence level of students, b=.0798, CI [.0427-.1189]. The authors, by their findings, called for innovative and practical teaching and learning in various universities in Ghana by lecturers and students
48p,; ill
Keywords: Knowledge Economy; University Preparation; Students Preparation; Globalisation